Multicenter Study of Homocysteine Measurement – Performance Characteristics of Different Methods, Influence of Standards on Interlaboratory Agreement of Results - Tripodi, Armando; Chantarangkul, Veena; Lombardi, Rossana; Lecchi, Anna; Mannucci, Pier Mannuccio; Cattaneo, Marco; for the ad hoc Study Group (Thrombosis and Haemostasis, 2001)
After the demonstration that moderate hyperhomocysteinemia is associated with thrombosis, many hematological labs are becoming interested in total homocysteine (tHcy) measurement. This prompted us to organize a collaborative study to investigate the performance of methods used in this setting and to assess the between-lab comparability of results. Two pairs of pooled plasma (A1-A2 and B1-B2) were prepared at the coordinating Center. tHcy levels were normal in A1-A2 and moderately high in B1-B2. Within each pair tHcy levels were similar but not identical. Aliquots were taken from each pool to prepare sets of 100 samples (coded from 1 to 100). Each set consisted of 25 replicates for each pool. Samples were frozen and shipped in dry ice to 16 labs with a common frozen aqueous standard. Labs were asked to measure (in blind) tHcy with their methods and standards. Results were sent to the coordinating Center both as raw readings and as tHcy levels. The following methods were used: High Pressure Liquid Chromatography (HPLC) in 12 labs (home-made in 10 and commercial in 2); Enzyme Immuno Assays (EIA) in 2; Fluorescence Polarization Immunoassay (FPIA) in 2 and Capillary Electrophoresis (CE) in one. Results for paired pools (A1-A2 and B1-B2) were analyzed by the Student t test to assess for the ability to discriminate between similar but not identical tHcy levels. Results for each pool were used to assess within-lab reproducibility and between-lab comparability. Within-lab reproducibility expressed as median CV ranged from 12.6 to 13.9% (home-made HPLC); from 9.2 to 11.4% (commercial HPLC); from 21.8 to 24.2% (EIA); from 2.7 to 3.3% (FPIA) and from 11.2 to 22.0% (CE). All labs, except one using CE and 2 using home-made HPLC, were able to discriminate between similar tHcy levels in the normal range (pools A1-A2). Ten labs (4 using home-made HPLC, 2 commercial HPLC, 2 FPIA, one EIA and one CE) were able to discriminate between similar moderately high tHcy levels (pools B1-B2). Between-lab comparability expressed as CV was 14.0% 13.9%, 15.6% and 14.5% for pools A1, A2, B1, and B2. These values were considerably lower (CV values < 5.2%) when a common plasma standard was used for calculation of tHcy levels, while the use of a common aqueous standard failed to achieve the necessary harmonization. In conclusion, performance characteristics of the FPIA method compare favorably with the well-established HPLC methods. It is simpler and more suitable to be used by general hematological labs. Between-lab comparability of results is still a problem. The establishment of an international plasma standard would be of help to harmonize tHcy measurement across laboratories.
Keywords: Homocysteine; standardization; thrombosis